Pelatihan Etika Bisnis dalam Meningkatkan Pemahaman pada para Pelaku UMKM - Mustika, Hindah; Hadi Santoso, Bambang; Arini, Dian; Lestariningsih, Marsudi (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Entrepreneur is something that has an important role in improving the economy and especially the welfare of a person or group of people. The focus of someone's desire to become an entrepreneur is because of a motivation, both internal and external. This existing motivation has a role so that entrepreneurs can run the business according to expectations, this sustainability certainly needs to be supported not only in terms of soft skills but also hard skills that need to be provided. The purpose of this service is to provide training in increasing understanding regarding business ethics, so that activities or activities that are already running can be better due to understanding and practice in the form of following norms or rules related to business ethics. The implementation method used in this study: preparation or outreach, training and mentoring. The results of this study are that MSME actors can utilize and apply business ethics in improving business so that a goal can be achieved in the form of continuous prosperity and sustainability. Keywords: Entrepreneur, Entrepreneurship, business ethics